Ergonomic Risk Analysis of Musculoskeletal Disorders (MSDs) Using ROSA and REBA Methods On Administrative Employees Faculty Of Science - Achmad Nuzul Amri; Boy Isma Putra (Journal of Applied Engineering and Technological Science (JAETS), 2022)
In administrative tasks, computers really need help so they can get the job done quickly and efficiently. Computers in the administration department are managed by a job that runs continuously for eight hours. Improper work posture and posture can cause fatigue and discomfort at work. One of the influencing factors is the working posture and body posture during these activities. This study aims to reduce the level of risk gained by performing Rapid Office Strain Assessments (ROSA) and Rapid Entire Body Assessments (REBA) for clerical staff in engineering departments. Posture analysis data processing using the ROSA (Rapid Office Strain Assessment) method found that five of her employees surveyed were at risk levels and needed to be corrected immediately. The Rapid Entire Body Assessment (REBA) method shows that five employees are currently at risk of urgent needs and requirements.